2003
DOI: 10.1191/0961203303lu474oa
|View full text |Cite
|
Sign up to set email alerts
|

Poor prognosis of end-stage renal disease in systemic lupus erythematosus: a cohort of Chinese patients

Abstract: We studied the clinical course of 26 systemic lupus erythematosus (SLE) patients who started regular dialysis at our hospital and whose stay exceeded a three-month duration in order to investigate the long-term prognosis in a Chinese cohort. Clinical and serological activities of lupus before and after dialysis were analysed. To compare the long-term survival rate, controls were set using 78 age-matched end-stage renal disease (ESRD) patients who did not have SLE or diabetes mellitus and entered the chronic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…The impairment of polymorphonuclear leukocyte phagocytosis in dialysis patients is aggravated in SLE patients receiving immunosuppressive agents [13] . In SLE patients on dialysis, infection was the major cause of mortality in a study by Lee et al [3] . In our SLE dialysis patients, however, HD and PD patients did not differ in the use of immunosuppressive medications (75.0 vs. 79.2%, p = 0.757).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The impairment of polymorphonuclear leukocyte phagocytosis in dialysis patients is aggravated in SLE patients receiving immunosuppressive agents [13] . In SLE patients on dialysis, infection was the major cause of mortality in a study by Lee et al [3] . In our SLE dialysis patients, however, HD and PD patients did not differ in the use of immunosuppressive medications (75.0 vs. 79.2%, p = 0.757).…”
Section: Discussionmentioning
confidence: 98%
“…The survival rate of lupus patients on dialysis is comparable to that of non-SLE dialysis patients. Lee et al [3] and Krane et al [4] documented the poor prognosis of SLE dialysis patients but did not compare clinical outcome between different dialysis modalities. In the papers by Rietveld and Berden [5] , Mojcik and Klippel [6] and Goo et al [7] , the conclusions were that treatment of lupus patients with hemodialysis (HD) has comparable results as in non-lupus patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, studies have been published showing the persistence of lupus activity in patients undergoing maintenance dialysis. Krane et al [11] reported an increase in the incidence of flares and recently Goo et al [13] and Lee et al [16] also pointed to persistent serological activity in patients on chronic dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…We opted for a cross-sectional study that, in contrast with others [2,7,8,9, 16, 17], included a control group. The system used to assess disease activity was the SLEDAI due to its easy applicability and previous use in studies evaluating ESRD patients [18,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation